Lanthanum-cerium mixed rare earth corrosion-resistant twisted steel with yield strength of 400MPa and production method thereof
By optimizing the smelting and alloying process, adding lanthanum cerium mixed rare earth reinforced alloy core wire, 400MPa grade lanthanum cerium mixed rare earth corrosion-resistant rebar steel bars were prepared, which solved the problems of shortage of existing corrosion-resistant rebar resources and high cost, and achieved high strength and corrosion-resistant steel bar production.
Patent Information
- Application Number
- CN202411732047.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
In the production of existing corrosion-resistant steel bars, high content of nickel, chromium, molybdenum, vanadium and other elements are reliant on, resulting in resource shortages and high costs, making it difficult to meet the demand for threaded steel bars for construction.
By optimizing converter smelting, microalloyation, rare earth multi-form alloying technology, LF furnace refining and continuous casting, the core wire of lanthanum cerium mixed rare earth reinforced alloy was added to prepare lanthanum cerium mixed rare earth corrosion-resistant threaded steel bars with a yield strength of 400MPa grade.
The high strength, high plasticity and good corrosion resistance of lanthanum and cerium mixed rare earth steel bars have been achieved, which reduces the cost of alloying, extends the service life of steel, reduces the environmental protection burden, and rationally utilizes rare earth resources.
Smart Images

Figure CN119506717A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a threaded steel bar and a production method thereof, and in particular to a lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa and a production method thereof. Background Art
[0002] With the widespread promotion of the application of vanadium new energy batteries and the promotion of the mandatory national standard GB1499.2 "Steel for reinforced concrete Part 2: Hot-rolled ribbed steel bars", the demand for vanadium will continue to increase, the price will rise year by year, and the resources will become less and less. Therefore, by utilizing the surplus rare earth resources such as lanthanum and cerium in northern my country, innovative lanthanum-cerium rare earth polymorphic alloying technology is formed to produce rare earth steel bars to improve the corrosion resistance of rebar. As a substitute for vanadium-nitrogen materials, rare earth reinforced alloys are cheap, have abundant resources, have the potential to improve the mechanical properties of rebar, and are expected to be applied and promoted in the market.
[0003] At present, corrosion-resistant steel bars mainly include stainless steel bars, epoxy resin coated steel bars, galvanized steel bars, stainless steel composite steel bars and nickel-chromium alloy corrosion-resistant steel. The characteristics of existing corrosion-resistant steel bars are high content of corrosion-resistant elements such as nickel, chromium, molybdenum, and vanadium, high price, and low output. As the country implements mandatory standards for construction steel bars, steel companies use micro-alloying to produce construction threaded steel bars, and the resources of strengthening and corrosion-resistant elements such as niobium, chromium, and vanadium are becoming increasingly scarce. Therefore, it is necessary to make full use of my country's surplus light rare earth resources such as lanthanum and cerium to produce corrosion-resistant steel bars to replace the pure corrosion-resistant alloy process to produce corrosion-resistant steel bars. Summary of the invention
[0004] One of the purposes of the present invention is to provide a lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa.
[0005] Specifically, a lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa contains the following elements: C 0.10-0.20%, Si 0.25-0.80%, Mn 0.90-1.60%, V 0.020-0.045%, Ti0.003-0.010%, P≤0.010%, S≤0.010%, Ni 0.25-0.65%, Cr 0.25-0.70%, RE (La, Ce) 0.10-0.18%, Cu≤0.20%, O≤0.004%, N≤0.006%, and the rest are Fe and unavoidable impurities.
[0006] The second object of the present invention is to provide a production method for the above-mentioned lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa, the steps including converter smelting, argon blowing refining, LF furnace refining, continuous casting and rolling, wherein rare earth reinforced alloy cored wire and silicon-calcium wire are fed into the molten steel during argon blowing refining.
[0007] During the argon blowing refining, 2000m-3500m of lanthanum-cerium mixed rare earth reinforced alloy cored wire is fed into the molten steel at a wire feeding speed of 2.5-3.0m / s, and the soft blowing time is ≥3 minutes, and then ≥150m of silicon-calcium wire is fed. After feeding the silicon-calcium wire, the argon blowing time is ensured to be ≥3 minutes.
[0008] During the argon blowing refining, the argon pressure is adjusted to 0.2-1.0Mpa depending on the tumbling of the molten steel. From the time the molten steel enters the station to the early stage of calcium treatment, the size of the argon bubble is controlled at 200mm-600mm. After the molten steel is fed into the calcium wire, the size of the argon bubble is controlled at 200mm-400mm.
[0009] During the LF furnace refining, the composition of the molten steel is adjusted so that FeO+MnO=1.04% in the final slag, the slag forming speed is fast, and the desulfurization rate is high.
[0010] Specifically, when the molten steel is 1529℃, the first batch of slag is added under strong stirring, 250NL of argon is added, and after slagging for 3 minutes, the second batch of slag is added, and the first power supply is 8 minutes, and aluminum particles, carburizer and slag-making deoxidizer are added; after the first power supply, strong stirring is carried out for 3 minutes, and when the molten steel reaches 1595℃, ferrosilicon, manganese silicon alloy, high carbon ferrochrome, nickel iron and vanadium nitrogen alloy are added, power is supplied for 1 minute, 500NL of argon is stirred for 2 minutes, and high carbon ferrochrome, nickel iron and manganese silicon alloy are added; when the molten steel is 1560℃, power is supplied for 3 minutes, carbon powder is added during the process, 300m of wire is fed, and vanadium nitrogen alloy is added; the molten steel is in the station for 55 minutes, the refining power supply time is 15 minutes, and soft blowing is 5 minutes; when the molten steel leaves the LF furnace, SiCaBa wire is fed and argon is soft blown for 5 minutes.
[0011] In the continuous casting, a long nozzle is used to protect the pouring, the lower nozzle is immersed in the molten steel in the crystallizer to a depth of 80 to 120 mm, and the water flow rate of the crystallizer is controlled at 135 m 3 / h, the molten steel in the crystallizer must not be exposed.
[0012] Continuous casting casting system:
[0013]
[0014] Electromagnetic stirring parameters for continuous casting:
[0015] Crystallizer electromagnetic stirring parameters: current 300A-350A; frequency 3-5Hz.
[0016] Terminal electromagnetic stirring parameters: current 600A; frequency 5Hz.
[0017] During the rolling, the temperature of the soaking section of the continuous casting billet in the heating furnace is strictly controlled at 1080-1094°C, and the heating time is 60-120 minutes to avoid coarse structure; the temperature of the upper cooling bed is 920-1030°C, and when rolling the specifications of 12mm-25mm, the temperature of the upper cooling bed is controlled at 1000-1030°C; when rolling the specifications of 28mm-32mm, the temperature of the upper cooling bed is controlled at 920-950°C; the rolling speed is 12.2-15.5m / s.
[0018] Advantages of the present invention:
[0019] 1. The present invention specifically optimizes the converter smelting process, microalloying process, rare earth polymorphic alloying technology, LF furnace refining and inclusion removal process, continuous casting crystallizer electromagnetic stirring, continuous casting end electromagnetic stirring, automatic water distribution process, and hot rolling optimization of starting rolling temperature, reduction system, post-rolling controlled cooling and other hot rolling processes to obtain steel bars with good mechanical properties and corrosion resistance.
[0020] During the smelting process of molten steel, a lanthanum-cerium mixed rare earth reinforced alloy is added, that is, a lanthanum-cerium mixed rare earth reinforced alloy cored wire is added, and after converter smelting, refining, continuous casting and hot rolling, a lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar is obtained. The composition, inclusions and mechanical properties of the 400MPa grade lanthanum-cerium mixed rare earth steel bar produced by the present invention fully meet the technical requirements of steel bars, meet the quality control requirements, and have the advantages of high strength, high plasticity, corrosion resistance, etc. It not only prolongs the service life of steel, but also avoids painting and galvanizing, reduces the environmental burden, and is conducive to the rational application of resources.
[0021] 2. The present invention provides a method for producing 400MPa grade lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bars by adding lanthanum-cerium mixed rare earth reinforced alloy microalloying. The method can utilize the surplus light rare earth resources such as lanthanum and cerium in northern my country to innovatively form lanthanum-cerium rare earth polymorphic alloying, thereby improving the corrosion resistance of threaded steel bars through the effects of lanthanum-cerium rare earth elements such as inclusion deformation, interface aggregation, and stabilization of rust layer. The smelting, rolling process and anti-rust mechanism are different from other corrosion-resistant steel bar production processes.
[0022] 3. Lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bars significantly reduce alloying costs. Compared with galvanized steel with the same service life, the anti-corrosion cost can be reduced by more than 60%. From the perspective of greenness, lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bars are exempt from coating and plating, which extends the service life to 30 to 50 years and significantly reduces carbon emissions. The promotion and application of lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bars can rationally utilize my country's strategic rare earth resources.
[0023] 4. The present invention adopts nickel-chromium-vanadium microalloying process to feed lanthanum-cerium mixed rare earth reinforced alloy cored wire. The nickel-chromium-vanadium alloy and lanthanum-cerium mixed rare earth reinforced alloy cored wire have high yield rate, can accurately control the composition of molten steel, and improve the performance and corrosion resistance of steel bars.
[0024] 5. The LF furnace performs deoxidation, desulfurization, degassing, removal of non-metallic inclusions and adjustment of the composition and temperature of the molten steel to further improve the purity of the molten steel and obtain qualified molten steel with low gas content and low inclusion content.
[0025] 6. Continuous casting adopts crystallizer electromagnetic stirring and end electromagnetic stirring technology to effectively improve the internal structure of the ingot, increase the equiaxed crystal rate, and float the inclusions to obtain good ingot quality.
[0026] 7. Use dynamic water distribution and appropriately reduce the drawing speed to help reduce billet cracks.
[0027] 8. Different specifications are rolled at different heating temperatures, heating times and upper cooling bed temperatures to obtain steel with stable ferrite + pearlite structure and mechanical and corrosion resistance performance indicators. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a low-magnification image of the continuous casting ingot of lanthanum-cerium mixed rare earth corrosion-resistant steel.
[0029] Figure 2 This is the metallographic structure diagram of Ф16 lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar.
[0030] Figure 3 This is the metallographic structure diagram of Ф12 lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar.
[0031] Figure 4 This is the metallographic structure diagram of Ф28 lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar.
[0032] Figure 5 This is the LF furnace smelting process flow chart. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments.
[0034] The process circuit of the present invention:
[0035] The process route is blast furnace (coke, ore) → molten iron → converter (nickel-chromium-vanadium micro-alloying) → CAS (argon blowing, wire feeding, lanthanum-cerium mixed rare earth reinforced alloy cored wire) → LF (secondary refining) → continuous casting (electromagnetic stirring of crystallizer, electromagnetic stirring at the end, automatic water distribution) → rolling mill → rolled product.
[0036] 1. Ingredient Design
[0037] C can improve the tensile strength and yield strength of steel bars, but reduce their corrosion resistance.
[0038] Si can significantly increase the yield strength and fatigue strength of steel bars, but reduce their plasticity, toughness, ductility and strength-to-yield ratio.
[0039] Mn can improve the instantaneous strength of steel bars, but has no significant effect on ductility, endurance strength and creep strength.
[0040] The V element can refine the structure and grains of steel and increase the grain coarsening temperature, thereby enhancing the strength, toughness and wear resistance of steel. At the same time, V also improves the corrosion resistance of steel bars.
[0041] Cr, Ni and Cu can all improve the corrosion resistance of steel bars. Among them, Ni can make steel bars have high strength, high toughness, high resistance, good hardenability and corrosion resistance, especially for chloride ions Cl - The Ni element easily accumulates in the rust layer to form a protective rust layer, which can resist Cl - Cr can improve the anti-oxidation and oxidation resistance of steel bars, and can form a dense and complete oxide film between the rust layer on the steel surface and the steel matrix, which can effectively inhibit the corrosion of corrosive anions, especially Cl - Its corrosion resistance is worse than that of Ni.
[0042] RE rare earth elements improve corrosion resistance by deformation of inclusions, interface aggregation, stabilization of rust layer, etc., but too high RE elements will increase the amount of second phase in steel, so the RE composition design range is 0.10-0.18%.
[0043] In this embodiment, the basic components of the steel bar are: C: 0.10-0.20%, Si: 0.25-0.80%, Mn: 0.90-1.60%, V: 0.020-0.045%, Ti: 0.003-0.010%, P≤0.010%, S≤0.010%, Ni: 0.25-0.65%, Cr: 0.25-0.70%, Re (La, Ce): 0.10-0.18%, Cu≤0.20%, O≤0.004%, N≤0.006%, and the rest are Fe and unavoidable impurities.
[0044] 2. Preparation of molten iron
[0045] Molten iron is prepared in a blast furnace using coke and ore.
[0046] 3. Converter Smelting
[0047] 1. Loading amount: 130±8 tons, scrap steel addition amount 0~45t, add scrap steel first and then molten iron. Add 2000kg of micro-carbon ferrochrome after adding scrap steel.
[0048] 2. Slag making: early slag, good slag, thorough slag and final slag are made to stick together, and the basicity of the final slag is controlled at 2.8-3.5 to protect the furnace lining and prevent phosphorus return during steelmaking.
[0049]
[0050] 3. The first batch of lime should be added 3 minutes before blowing starts, accounting for 2 / 3-1 / 2 of the total amount; 3 minutes after blowing starts, the remaining 1 / 3-1 / 2 of lime should be added in batches until it is finished 3 minutes before lifting the gun; about 300kg of lime should be reserved to suppress splashing. If there is no splashing, add it 10 minutes before blowing.
[0051] 4. Add flux, the amount added should be less than 4kg / t, and the amount of flux should be adjusted according to the "drying back" and slag conditions.
[0052] 5. Add ore: Ore is used as slag flux in the early and middle stages and cooling agent in the later stage. It is added in batches according to the temperature and slag conditions. The amount added in each batch shall not exceed 500 kg. It is strictly forbidden to add ore 2 minutes before the end point.
[0053] 6. Add dolomite: dolomite is added with the first batch of lime; to protect the furnace lining, adjust the final slag MgO content to ≥8%; every 100 kg of light-burned dolomite added can be equivalent to 40 kg of lime.
[0054] 7. The oxygen flow rate and pressure of the converter oxygen lance must be strictly implemented in accordance with the following regulations:
[0055]
[0056] 8. The blowing end point is determined based on the carbon flame and carbon flower appearance combined with oxygen supply time and oxygen consumption. The smelting process adopts the "high-pull compensation method" or the one-time carbon pulling method. End point: [C]: 0.05% ≤ [C] ≤ 0.15%, [P] ≤ 0.035%, [S] ≤ 0.040%, and the number of post-blows is strictly controlled to be ≯ 1 time.
[0057] 9. Add slag stopper rods to stop slag when 1 / 2 to 2 / 3 of the steel is tapped to ensure that the slag under the ladle is ≤50mm. After the steel is tapped and the slag stopper rods are poked, add the slag stopper plugs.
[0058]
[0059]
[0060] 10. The steel is sent to the argon blowing station for refining. 200kg synthetic slag, 20-60kg deoxidizer Si-Al-Ba, and 20-40kg deoxidizer Si-Ca-Ba are added to the steel.
[0061] 4. Refining at Argon Blowing Station
[0062] 1. During the steel-making process, the argon gas should be controlled so that the molten steel does not splash out of the molten steel tank. The argon gas pressure is adjusted to 0.2-1.0Mpa according to the tumbling of the molten steel. From the time the molten steel enters the station to the early stage of calcium treatment, the size of the argon bubble is controlled at 200mm-600mm. After the molten steel is fed into the calcium line, the size of the argon bubble is controlled at 200mm-400mm.
[0063] 2. Take samples and measure the temperature after the molten steel enters the station. Feed 2000m-3500m of lanthanum-cerium mixed rare earth reinforced alloy cored wire into the molten steel at a feeding speed of 2.5-3.0m / s, and the soft blowing time is ≥3 minutes, and then feed ≥150m of silicon-calcium wire. After feeding the silicon-calcium wire, ensure that the argon blowing time is ≥3 minutes.
[0064] 3. According to the incoming composition and temperature, make fine adjustments to the composition and temperature. After adding the alloy or scrap steel, ensure that the argon blowing lasts for ≥3 minutes. Take temperature measurements and samples to ensure that the composition and temperature are qualified before going on stage.
[0065] 4. After the argon blowing station is operated, add 50-60kg of molten steel insulation material before leaving the station.
[0066] 5. LF furnace refining
[0067] LF furnace smelting process flow see Figure 5 .
[0068] 1. After entering the station, take sample L1, measure the temperature at 1529℃, add the first batch of slag under strong stirring, argon 250NL, slag at 12 gear for 3 minutes, then switch to 4 gear, and add the second batch of slag in batches. The first power supply lasts for 8 minutes, and 10kg aluminum particles, 10kg carburizer, and 20kg slag deoxidizer are added. The LF furnace has 12 working voltage gears. The voltage of gear 12 is 290V and the current is 42000A; the voltage of gear 4 is 380V and the current is 42000A. Strong stirring refers to stirring with argon gas blowing when the argon flow rate is ≥500NL.
[0069] 2. After the first power supply, stir vigorously for 3 minutes, take sample L2, and measure the temperature at 1595℃. Add 313kg of ferrosilicon, 60kg of manganese silicon alloy, 100kg of high carbon ferrochrome, 85kg of nickel iron, and 2kg of vanadium nitrogen alloy, supply power for 1 minute, stir for 2 minutes with 500NL of argon, and take sample L3. Add 300kg of high carbon ferrochrome, 100kg of ferrochrome (300kg in total), 100kg of nickel iron, and 380kg of manganese silicon alloy, measure the temperature at 1560℃, supply power for 3 minutes, add 40kg of carbon powder during the process, feed the wire for 300m, add 2kg of vanadium nitrogen alloy, and take out sample L5.
[0070] 3. The molten steel stays in the station for 55 minutes, the refining power supply time is 15 minutes, and the soft blowing time is 5 minutes.
[0071] 4. When the LF furnace leaves the station, 360 meters of SiCaBa wire is fed and soft argon is blown for 5 minutes.
[0072] 5. Slag sample analysis:
[0073]
[0074] In the refined slag 1, FeO+MnO=1.04%, the final slag is off-white, the slag forming speed is fast, and the desulfurization rate is high.
[0075] 6. Continuous Casting
[0076] 1. Use long nozzle to protect pouring.
[0077] 2. The molten steel in the tundish must not be exposed.
[0078] 3. The opening liquid level of the tundish is ≥300mm or the amount of molten steel is ≥10 tons, the normal liquid level is ≥650mm or the amount of molten steel is ≥28 tons, and the liquid level in the tundish remains relatively stable.
[0079] 4. Use ultra-high casting speed protection slag for the crystallizer and keep it dry.
[0080] 5. The depth of the water outlet immersed in the molten steel in the crystallizer is 80 to 120 mm.
[0081] 6. The crystallizer water flow rate is controlled at 135m 3 / h, the molten steel in the crystallizer must not be exposed.
[0082] 7. Wheel throwing system
[0083]
[0084]
[0085] 8. Electromagnetic stirring parameters:
[0086] Crystallizer electromagnetic stirring parameters: current: 300A-350A; frequency: 3-5Hz.
[0087] End electromagnetic stirring parameters: current: 600A; frequency: 5Hz.
[0088] 9. Water distribution system
[0089]
[0090] Linear water distribution is adopted, Y=Ax+B, where Y is the total flow, A is the coefficient, and B is a fixed value (zone 1+zone 2+zone 3+zone 4=between 1.71-1.73).
[0091] 10. Low-power quality
[0092] Figure 1 This shows that the water distribution system is reasonable, the low-magnification quality of the continuous casting billet is good, and there is only a 0.5-level central porosity defect.
[0093] 7. Rolling
[0094] 1. Rolling process parameters:
[0095]
[0096] In the heating furnace, the temperature of the soaking section of the continuous casting billet is strictly controlled at 1080-1094℃, and the heating time is 60-120min to avoid coarse structure; the temperature of the upper cooling bed is 920-1030℃. When rolling 12mm-25mm specifications, the temperature of the upper cooling bed is controlled at 1000-1030℃; when rolling 28mm-32mm specifications, the temperature of the upper cooling bed is controlled at 920-950℃; the rolling speed is 12.2-15.5m / s.
[0097] 2. Mechanical properties
[0098]
[0099] 3. Metallographic structure
[0100] The metallographic structure is F+P, and the grain size grade is 8.5-9.5.
[0101] Specification Metallographic structure Grain size Inclusion Ф16 F+P 9.0 D 0.5 Ф12 F+P 9.0-9.5 C 0.5 Ф28 F+P 8.5-9.0 C 0.5, D 0.5
[0102] 4. Corrosion resistance
[0103] The corrosion test adopts YB / T4367-2014 "Rebar Corrosion Test Method in Chloride Ion Environment". The sample immersion cycle is 144 hours. The test results show that the average corrosion rate of ordinary HRB400 is 4.8983-5.1928g / m 2 .h, the average corrosion rate of lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bars is 3.0118-3.2589g / m 2 ·h, the relative corrosion rate is 58%-66.53%.
Claims
1. A 400MPa grade lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar, characterized in that: It contains the following elements: C 0.10-0.20%, Si 0.25-0.80%, Mn 0.90-1.60%, V 0.020-0.045%, Ti 0.003-0.010%, P≤0.010%, S≤0.010%, Ni 0.25-0.65%, Cr 0.25-0.70%, RE 0.10-0.18%, Cu≤0.20%, O≤0.004%, N≤0.006%, and the rest is Fe and unavoidable impurities.
2. The production method of the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa as claimed in claim 1, the steps comprising converter smelting, argon blowing refining, LF furnace refining, continuous casting, and rolling, characterized in that: During the argon blowing refining, lanthanum-cerium mixed rare earth reinforced alloy core wire and silicon-calcium wire are fed into the molten steel.
3. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: During the argon blowing refining, 2000m-3500m of lanthanum-cerium mixed rare earth reinforced alloy cored wire is fed into the molten steel at a wire feeding speed of 2.5-3.0m / s, and the soft blowing time is ≥3 minutes, and then ≥150m of silicon-calcium wire is fed. After feeding the silicon-calcium wire, the argon blowing time is ensured to be ≥3 minutes.
4. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: During the argon blowing refining, the argon pressure is adjusted to 0.2-1.0Mpa depending on the tumbling of the molten steel. From the time the molten steel enters the station to the early stage of calcium treatment, the size of the argon bubbles is controlled at 200mm-600mm. After the molten steel is fed into the calcium wire, the size of the argon bubbles is controlled at 200mm-400mm.
5. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: During the LF furnace refining, the composition of the molten steel is adjusted so that FeO+MnO=1.04% in the final slag.
6. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 5, characterized in that: When the molten steel is 1529℃, the first batch of slag is added under strong stirring, with an argon flow rate of 250NL. After slagging for 3 minutes, the second batch of slag is added, and the first power supply is 8 minutes. Aluminum particles, carburizer and slag-making deoxidizer are added; after the first power supply, strong stirring is carried out at an argon flow rate of 500NL for 3 minutes. When the molten steel reaches 1595℃, ferrosilicon, manganese silicon alloy, high carbon ferrochrome, nickel iron and vanadium nitrogen alloy are added. Power is supplied for 1 minute and stirred for 2 minutes with an argon flow rate of 500NL, and high carbon ferrochrome, nickel iron and manganese silicon alloy are added; when the molten steel is 1560℃, power is supplied for 3 minutes, and carbon powder is added during the process. 300m of 3:42 wire is fed, and vanadium nitrogen alloy is added; the molten steel is in the station for 55 minutes, the refining power supply time is 15 minutes, and soft blowing is 5 minutes; SiCaBa wire is fed into the molten steel when it leaves the LF furnace, and soft argon blowing is carried out for 5 minutes.
7. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: In the continuous casting, a long nozzle is used to protect the pouring, the lower nozzle is immersed in the molten steel in the crystallizer to a depth of 80 to 120 mm, and the water flow rate of the crystallizer is controlled at 135 m 3 / h, the molten steel in the crystallizer should not be exposed.
8. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: In the continuous casting, the superheat is 8-12°C, the pulling speed is 4.6m / min; the superheat is 13-16°C, the pulling speed is 4.5m / min; the superheat is 17-19°C, the pulling speed is 4.4m / min; the superheat is 20-22°C, the pulling speed is 4.3m / min; the superheat is 23-25°C, the pulling speed is 4.2m / min.
9. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: During the continuous casting, the crystallizer electromagnetic stirring parameters are: current 300A-350A; frequency 3-5Hz; the end electromagnetic stirring parameters are: current 600A; frequency 5Hz.
10. The method for producing the lanthanum-cerium mixed rare earth corrosion-resistant threaded steel bar with a yield strength of 400 MPa according to claim 2, characterized in that: During the rolling, the temperature of the soaking section of the continuous casting billet in the heating furnace is controlled to be 1080-1094°C, and the heating time is 60-120min; the temperature of the upper cooling bed is 920-1030°C, and when rolling the 12mm-25mm specification, the temperature of the upper cooling bed is controlled at 1000-1030°C; when rolling the 28mm-32mm specification, the temperature of the upper cooling bed is controlled at 920-950°C; the rolling speed is 12.2-15.5m / s.
Citation Information
Cited By
400MPa-grade low-temperature corrosion-resistant steel bar for frozen soil engineering and preparation method of low-temperature corrosion-resistant steel bar
CN121718804A
A low-temperature corrosion-resistant steel bar for 400MPa grade frozen soil engineering and its preparation method
CN121718804B
Production method of anti-corrosion Q355B plate with micro rare earth content
CN121874632A